Comparison of Short-Term Hearing Outcome in Stapedotomy Using either Vein or Fat (Adipose Tissue) as Sealing Material - Velusamy, Anand; Kavithadevi, A.; Hameed, Nazrin; Anand, Aishwarya (International Archives of Otorhinolaryngology, 2023)
Introduction Otosclerosis is a common cause of conductive hearing loss in the adult population that is caused by fixation of the stapes footplate. Cochlear otosclerosis may also present with sensorineural or mixed hearing loss. Surgery is the definitive treatment of choice and, during the procedure, sealing of the oval window with autologous tissue graft around the stapes prosthesis has been routinely done to improve hearing outcome and to mitigate postoperative complications.Objective To evaluate the efficacy of two different types of autologous tissue (vein or fat) grafts as oval window sealing materials in stapedotomy in improving short-term hearing outcomes.Methods In our study, 70 patients with otosclerosis who underwent primary stapedotomy were included. They were divided into group 1 (vein graft) and group 2 (fat graft) based on the type of sealing material used. All patients were followed-up at the end of 3 months, undergoing an audiometric examination to assess the hearing outcome.Results A total of 80% (n = 28) of the patients in group1 had an air-bone gap (ABG) closure < 10dB, and, in group 2, 85.7% had an ABG closure < 10 dB; this difference was found to be statistically insignificant. A total of 42.9% (n = 15) of the patients in group 1 and of 31.4% (n = 11) in group 2 had a significant improvement in bone conduction, while 14.3% (n = 5) of the patients in group 1 and 17.1% (n = 6) in group 2 had worsening of average bone conduction postoperatively, which was found to be statistically insignificant.Conclusion Both vein and fat grafts had comparable effects on hearing outcomes when used as sealing materials in stapedotomy.
Keywords: otosclerosis; otospongiosis; stapes surgery; hearing loss; stapedectomy